Youths’ awareness and attitudes towards raising the minimum legal age of smoking and passive smoking in Singapore - Gunasekaran, Kalaipriya; Singh, Prashwin; Ng, Ding Xuan; Koh, Eileen Yi Ling; Lee, Huan Yu; Tan, Rei; Wang, Yier; Tan, Ngiap Chuan (Frontiers in Public Health, 2024)
Objectives Early smoking initiation has been associated with a higher risk of developing long-term smoking habit. There is a growing global consensus that demands raising the minimum legal age (MLA) for smoking as an approach to address this problem. Singapore successfully raised the MLA from 18 to 21 years in 2021. This study aimed to evaluate the awareness and attitude of multi-ethnic Asian youth (aged 15–24) on raising MLA to 21 and passive smoking. Methods A cross-sectional survey comprising of 23 items was circulated via a secure internet-based platform, FORMSG between September and November 2022. Data were analyzed for descriptive statistics. Categorical variables were compared for association with receptivity toward change in MLA using Chi-Squared test and multivariable logistic regression analysis using Rstudio. Post-hoc Bonferroni correction were further utilized for pairwise comparison. Results Majority (80.3%) of the 608 participants expressed their support for MLA 21 implementation. Participants’ age was a significant variable as those aged 15–17 years old (OR = 2.1, 95%CI = 1.01–4.32, p = 0.048) showed a higher likelihood of supporting MLA implementation compared to those aged 21 and above. In addition, majority (89.8%) of them were also aware of the harmful effects of passive smoking. When it came to discouraging smoking among youth, family influence (64%) and school education (55.6%) emerged as the top strategies. Conclusion Most of the youth express strong support for raising the MLA to 21, with over 80% in favor of such change, reflects a significant harmony among youth in favor of tobacco-free environment.